Peran Nilai Budaya Lokal Dalam Memengaruhi Preferensi Desain UI/UX Aplikasi Maxride Di Kalangan Mahasiswa Universitas Hasanuddin - Astrina Wulan Putri; Eliyah Acantha Manapa Sampetoding; Muhammad Hasbi; Riskawati Riskawati (UNIVED Press, 2025)
— ASTRINA WULAN PUTRI. The Role of Local Cultural Values in Influencing UI/UX Design Preferences of the Maxride Application Among Students of Hasanuddin University (supervised by Eliyah Acantha Manapa Sampetoding).Background.Indonesia is a multicultural country with various local cultures that influence preferences in the use of technology, including UI/UX design of applications. In South Sulawesi, cultural values such as Tabe and the 3S Principles (Sipakatau, Sipakalebbi, Sipakainge’) significantly affect user behavior when interacting with applications. Objective.This study aims to examine the relationship between local cultural values and the UI/UX design preferences of the Maxride application, as well as to test the influence of local wisdom on design elements such as color, iconography, layout, and navigation. Method.This study employs a Mixed-Methods Approach (Quantitative and Qualitative), involving 193 respondents through a Likert scale survey and a Focus Group Discussion (FGD) with 15 participants. Data analysis was performed using triangulation to strengthen the validity of the results. Results.The quantitative study revealed a significant relationship between the UI/UX design elements of the Maxride application and local cultural values, with a Cronbach’s alpha value of 0.952. The qualitative study showed that local cultural values influence user preferences regarding design elements such as color, icons, and navigation.Conclusion. Local cultural values play an essential role in shaping user preferences for the UI/UX design of the Maxride application. By integrating these cultural values, user satisfaction with the design can be improved.